Analisis Spasial Faktor-Faktor yang Mempengaruhi Prevalensi Ketidakcukupan Konsumsi Pangan di Indonesia Tahun 2020 - Aryadi Solana (Seminar Nasional Official Statistics, 2022)
Prevalence of Undernoursihment (PoU) is one of the indicators that is a benchmark for achieving the goals of SDG's (2) Zero Hunger. During the Covid-19 pandemic, prevalence of undernoursihment (PoU) in Indonesia increased in 2020 compared to 2019. This study aims at the factors that influence PoU at the provincial level in Indonesia in 2020. Spatial influences need to be taken into account because there is spatial autocorrelation on the prevalence of undernoursihment between provinces, so that the direct and indirect effects of the factors used are also analyzed. From the use of the Spatial Autoregressive Confused (SAC) regression model, it is known that the increase in per capita expenditure, per capita rice production, and the realization of per capita local government social assistance spending have a significant effect in reducing the prevalence of undernoursihment. On the other hand, the increase in average monthly food inflation has a significant effect on increasing the prevalence of undernoursihment. One of the suggestions of this study is that there needs to be government attention in further studying the level of food inflation. Food inflation that occurs without being accompanied by an increase in people's purchasing power, but is caused by the scarcity of raw materials and resources will further reduce the level of public welfare and will have an impact on increasing the prevalence of undernoursihment.